(m, C)-Isometric Toeplitz operators with rational symbols. Issue 19 (16th December 2022) - Ko, Eungil; Lee, Ji Eun; Lee, Jongrak
ABSTRACT: An operator T ∈ L ( H ) is said to be ( m, C )-isometric if there exists a conjugation C such that 1 ∑ j = 0 m ( − 1 ) m − j ( m j ) T ∗ j C T j C = 0 for some positive integer m . In this paper, we study ( m, C )-isometric Toeplitz operators T φ with rational symbols φ . We characterize ( m, C )-isometric Toeplitz operators T φ by properties of the rational symbols φ . Moreover, we provide a concrete description of the ( m, C ) -isometric block Toeplitz operators.